Political Transformation, Ethnic Composition And Socio-Military Processes In The Khiva Khanate (18th–19th Centuries) (Eurasian Journal of History, Geography and Economics, 2026)
This article examines the political transformations, ethnic composition, and sociomilitary developments in the Khiva Khanate from the second half of the 18th century to the late 19th century. Special attention is given to the rise of the Qongirat dynasty, the weakening of central authority, and the role of tribal elites in shaping the political system. The study analyzes the increasing importance of Turkmen tribes as a military and political force, as well as their complex relationship with the khanate authorities. Furthermore, the article explores the processes of population resettlement, the expansion of slave trade, and the impact of Russian imperial expansion on the region. The research also highlights the regional differences in ethnic composition between southern agricultural areas and the Aral Sea region, as well as the historical formation of the Uzbek ethnonym.